2008
DOI: 10.1038/nature07350
|View full text |Cite
|
Sign up to set email alerts
|

The ion pathway through the opened Na+,K+-ATPase pump

Abstract: P-type ATPases pump ions across membranes, generating steep electrochemical gradients that are essential for the function of all cells. Access to the ion-binding sites within the pumps alternates between the two sides of the membrane1 to avoid the dissipation of the gradients that would occur during simultaneous access. In Na+,K+-ATPase pumps treated with the marine agent palytoxin, this strict alternation is disrupted and binding sites are sometimes simultaneously accessible from both membrane sides, transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
59
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 30 publications
4
59
0
Order By: Relevance
“…Although our data suggest that this pathway cannot accommodate NMG ϩ (mean diameter 7.3 Å) (32), consistent with the inability of NMG ϩ to inhibit the pump in a voltagedependent manner, we cannot be sure whether this access channel is narrower than the pathway opened by palytoxin on the Na/K-ATPase (33). Palytoxin opens a pathway large enough to accomodate organic cations as large as NMG ϩ (although with 50ϫ lower permeability than Na ϩ ) and may represent the exposed pathway for access to and from the shared binding sites (34).…”
Section: Discussionmentioning
confidence: 99%
“…Although our data suggest that this pathway cannot accommodate NMG ϩ (mean diameter 7.3 Å) (32), consistent with the inability of NMG ϩ to inhibit the pump in a voltagedependent manner, we cannot be sure whether this access channel is narrower than the pathway opened by palytoxin on the Na/K-ATPase (33). Palytoxin opens a pathway large enough to accomodate organic cations as large as NMG ϩ (although with 50ϫ lower permeability than Na ϩ ) and may represent the exposed pathway for access to and from the shared binding sites (34).…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, the green spheres represent the set of possible positions of the dummy particle, and the large transparent green sphere of 10-Å radius centered on the average optimal position indicates the overall region where the fluorophore might be located based on this analysis. A Bodipy-Fl Ouabain molecule was then inserted into a physically reasonable position, with the fluorophore moiety as close as possible to the 10-Å radius sphere and the ouabain moiety of the fluorescent inhibitor oriented to block the ion permeation pathway of the pump located between TM1, TM2, TM4, and TM6 (24). In the model, the high affinity binding site for ouabain is located in close proximity to residues identified in a previous site-directed mutagenesis study (36) (Fig.…”
Section: Lret Measurements Between External Linkers Of the Namentioning
confidence: 99%
“…In both structures, ouabain sits in a cleft between transmembrane (TM) 5 segments TM1, TM2, TM4, TM5, and TM6. Interestingly, many of these TMs have been implicated in the formation of the ion permeation pathway (23,24), suggesting that ouabain might directly block access of ions to their binding sites.…”
mentioning
confidence: 99%
“…The recently published crystal structure of the Na + ,K + -ATPase phosphoenzyme (E2P) in complex with the widely studied CTS ouabain (4,5) showed that the high-affinity CTS-binding site is constituted by the transmembrane helices αM1-6 of the catalytic α-subunit, forming a pocket exposed to the extracellular side and overlapping with the extracellular ion exchange pathway (6). The E2P-ouabain structure also revealed details on proteinligand interactions facilitating high-affinity CTS binding compared with a low-affinity ouabain complex (7).…”
mentioning
confidence: 99%